Arrangement of Agricultural Land Production Sharing Agreements in the Development of Environmentally Friendly Agrotourism - Dewi Susilawati, Ni Putu; Sriasih Wesna, Putu Ayu; Alit Puspadma , I Nyoman (Journal Research of Social Science, Economics, and Management, 2022)
One model of tourism development that is in line with alternative tourism is community-based tourism as a pattern that is believed to provide economic benefits and equity, environmental preservation, local culture preservation, social empowerment, community empowerment. Community-based tourism is a tourism development with a high level of local community involvement and can be accounted for from the socio-cultural and environmental aspects. So far, there are no clear rules that explicitly regulate the arrangement of profit sharing, especially in the field of agro-tourism. According to Article 1320 of the KUHPerdata, an agreement is valid if it meets the following four conditions: Agree of those who bind themselves, The ability to make an engagement, a certain thing, a lawful cause—referring to the Legal Principles of Agreement as contained in the KUHPerdata (KUHPerdata), namely Personality Principles (Article 1315 jo 1340 KUHPerdata), Consensualotas Principles (Article 1320 KUHPerdata), Freedom of Contract Principles (Article 1338 paragraph (1) KUHPerdata). In the current reformation era, the legal development strategy is directed towards responsive law characterized by the large role of judicial institutions and the broad participation of social groups or the participation of individuals in society to determine the direction of legal development, resulting in the formation of clear legislation. Furthermore, provide legal certainty in making agreements for agricultural land products related to agro-tourism with environmental insight.